The Application of Justice Principles in Sentencing Criminal Sanctions for Defamation Convicts Through Electronic Media - The Mei Djoen; Tanudjaja Tanudjaja (International Journal Labs, 2025)
The rapid development of digital technology and social media in Indonesia has transformed the landscape of public interaction and expression. However, this progress is accompanied by a significant increase in defamation cases through electronic media, creating complex challenges for law enforcement and the application of the principle of justice. This research aims to analyze the application of justice principles and the effectiveness of legal remedies in imposing criminal sanctions against convicted individuals for defamation through electronic media, based on five court decisions in Indonesia. The issues examined include: (1) how justice principles are applied in criminal verdicts for defamation cases through electronic media; and (2) to what extent legal remedies are effective in addressing sentencing disparities in cases with similar legal elements. The research method used is normative juridical, with a case and statutory approach. The findings reveal significant variation in the application of justice by judges, ranging from imprisonment to suspended sentences, depending on judicial sensitivity to social context and understanding of freedom of expression. On the other hand, the effectiveness of legal remedies is generally weak, especially in cases brought to the Supreme Court, where substantive legal arguments are not accommodated. The study recommends reform in cybercriminal law and the development of sentencing guidelines specifically for Electronic Information and Transaction Law-related offenses. The research analyzed five court decisions showing disparities in criminal sanctions despite similar legal elements, indicating inconsistent application of legal certainty and justice principles that should serve as the foundation of criminal law.